Karakteristik Pencetus Hiperbilirubinemia pada Neonatus di Rumah Sakit Daerah Mangusada Badung Bali Periode 2022-2023 - I Putu Agung Dhrestaketu Sumedang; Romy Windiyanto; Ni Wayan Armerinayanti (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
World Health Organization in 2019 reported that as many as 7000 newborns died in the world, while in Indonesia as many as 185 newborns died per day with an IMR of 15/1000 live births. In Mangusada Badung regional hospital, the incidence of neonates with hyperbilirubinemia in 2017 was 1100 neonates, in 2018 there were 1151 neonates with hyperbilirubinemia and in 2019 there were 1075 babies with neonatal jaundice. Hyperbilirubinemia is an increase amount of bilirubin that accumulates in the blood, characterized by total serum bilirubin levels ? 5 mg/dL (86 µmol/L). This study aims to determine the characteristics of triggers of hyperbilirubinemia in neonates at Mangusada Badung Regional Hospital Bali 2022-2023. This study used medical records of hyperbiliribinemia neonates at Mangusada Badung Regional Hospital Bali in periode 1st Januari-31st December 2023 to collect data. Then analysed univariat with descriptive analysis. The results of this study were the characteristics of the dominant variables including the age of the mother at risk (76,4%), male gender (62,2%), neonates with induction of labor (60,0%), premature neonates (81,3%), LBW (81,3%), asphyxia (95,5%), breastfeeding neonates (69,7%), and caesarean delivery method (68,5%). This study can be an additional information about the characteristics of hyperbilirubinemia triggers in neonates so that prevention can be done.